The information and communication technologies in the school - Sergio Briceño Castañeda; Andrés Castellanos (Corporación Universitaria Minuto de Dios, 2010)
This paper presents, in general lines, the elements of the educational proposal made from the Meta Digital Programme to accompany the incorporation of ICT(computer, internet, digital board) in the participating schools of this department. It also shows the reasons that lead to frame the proposal in a constructivism tendency, the elements that methodological strategy incorporates from problem-based learning (PBL), the meaning of accompaniment during the process and the role of the research component development of it.